2021
DOI: 10.1111/dar.13272
|View full text |Cite
|
Sign up to set email alerts
|

Summarising the impacts of the Queensland Alcohol‐related violence and Night‐Time Economy (QUANTEM) project

Abstract: This closing commentary to the special section presents an overview of the Queensland Alcohol-related violence and Night-Time Economy Monitoring evaluation findings in comparison to those from other jurisdictions where similar interventions have been implemented (such as Sydney and Newcastle), and especially with previous studies that have used similar evaluation methodologies, such as the Dealing with Alcohol and the Night-Time Economy study. Overall, the articles documented promising reductions in alcohol-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Each scanner is networked through central servers and the details of any banned person are downloaded to all venues operating a scanner within around ten minutes of the ban being imposed. The QUANTEM project undertook an evaluation of the TAFV policy in 15 SNPs (Miller et al 2017(Miller et al , 2019, and findings have been reported within a range of papers (Carah et al 2021;Ferris et al 2021;Miller et al 2021b;Taylor et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Each scanner is networked through central servers and the details of any banned person are downloaded to all venues operating a scanner within around ten minutes of the ban being imposed. The QUANTEM project undertook an evaluation of the TAFV policy in 15 SNPs (Miller et al 2017(Miller et al , 2019, and findings have been reported within a range of papers (Carah et al 2021;Ferris et al 2021;Miller et al 2021b;Taylor et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…39 The number of people entering licensed venues and moving through night-time precincts remained stable, and in some areas a greater diversification of entertainment offerings was observed. 40,41 This highlights the importance of documenting impacts beyond assaults and injuries, for example including impacts on nightlife and trade, in future studies.…”
Section: Discussionmentioning
confidence: 99%
“… 20–22 That study found that NTE regulation (that includes reduced trading hours) reduced alcohol harms without reducing the number of patrons, scale or diversity of NTEs and occurred while the number of alcohol licensed venues increased. 17 18 62 …”
Section: Discussionmentioning
confidence: 99%
“…The Queensland Alcohol-related violence and Night-Time Economy (QUANTEM) project provides an example of how such a study could be conducted, using multiple data sources to measure impacts on alcohol-related health and social harms and local economies. [17][18][19][20][21][22][23][24] Furthermore, the ExILEnS study and research stemming from the NIHR School for Public Health Research alcohol programme demonstrate how impacts of local alcohol policies have been evaluated in UK contexts. 13 15 16 25 A well-theorised, robust impact evaluation of the LNL is overdue.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation